2020
DOI: 10.3390/su12145709
|View full text |Cite
|
Sign up to set email alerts
|

Diversified Farms Facing the Covid-19 Pandemic: First Signals from Italian Case Studies

Abstract: The paper focuses on the effects of the Covid-19 pandemic on some Italian farms. In particular, the aim is to investigate the consequences of the health emergency on diversified farms, their reactions, and their agricultural and rural policy needs in order to overcome the crisis. The research path investigates five farms of central Italy through semi-structured interviews. The identified case studies are characterized by the heterogeneity of features and farms’ activities. These activities include agritourism,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 37 publications
(58 citation statements)
references
References 25 publications
3
47
0
8
Order By: Relevance
“…In particular, under these measures, in the first weeks of the pandemic, there was a considerable decline in labor productivity, higher labor and transportation costs, significant loss of income for farmers, food shortages and an increase in vulnerable products' prices such as vegetables and fruit for consumers (Ibidem). These measures have influenced and continue to strongly influence the structure of demand (Mastronardi et al, 2020) and, consequently, the entrepreneurial activity. Coordinated agricultural policy and programs are now needed so that the path to sustainable development is based on fair, green and healthy agri‐food systems (Blay‐Palmer et al, 2020).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 3 more Smart Citations
“…In particular, under these measures, in the first weeks of the pandemic, there was a considerable decline in labor productivity, higher labor and transportation costs, significant loss of income for farmers, food shortages and an increase in vulnerable products' prices such as vegetables and fruit for consumers (Ibidem). These measures have influenced and continue to strongly influence the structure of demand (Mastronardi et al, 2020) and, consequently, the entrepreneurial activity. Coordinated agricultural policy and programs are now needed so that the path to sustainable development is based on fair, green and healthy agri‐food systems (Blay‐Palmer et al, 2020).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…A feature of the pandemic has been a switch from face‐to‐face to digital connections (Phillipson et al, 2020). Research by Mastronardi et al (2020) has shown that online sales have increased significantly. The share of sales, which has been lost due to the closure of Farmers' Market (FM), has been replaced by an equal amount sold to non‐profit organizations, such as episcopal curia, at reduced prices.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…At the same time, it points out that impact monitoring should be continuous and long‐term since enterprises recover at different rates. During the first phase of COVID‐19, Italian farmers sought cooperation with volunteers and the social economy, or the third sector, in order to address its effects, including social enterprises (Mastronardi, Cavallo, & Romagnoli, 2020). Research by Lucaci and Nastase (2020) examining the rural business environment in Europe during the first phase of the COVID‐19 spread found that the pandemic negatively affected the lives of rural residents and the business activity of these areas.…”
Section: Literature Reviewmentioning
confidence: 99%